Tónlist liðinna alda íslensk handrit 1100-1800 - Árni Heimir Ingólfsson 1973- (Crymogea, 2019)
The first comprehensive history of Icelandic documented music from 1100-1800. The author, pianist and musicologist Árni Heimir Ingólfsson, has been tirelessly studying the history and various aspects of Icelandic music. He has written two major books on the subject already; Saga tónlistarinnar (2016) and Jón Leifs - Líf í tónum (2009). This is an admirable and much awaited study in the history and origin of music in Iceland.
Keywords: Geschichte 1100-1800; Geistliche Musik; Musikhandschrift; Island; Quelle; Kommentar